Associations of fish and meat intake with iron and anaemia in Malawian children - E. Rochelle Werner; Charles D. Arnold; Bess L. Caswell; Lora L. Iannotti; Kenneth M. Maleta; Christine P. Stewart (Wiley, 2024)
Abstract Animal flesh foods are rich in bioavailable iron but infrequently consumed by young children. We aimed to determine whether flesh food intake was associated with iron and anaemia status among 585 Malawian infants enroled in a 6‐month egg‐feeding trial. The percentage of days of small fish, large fish and meat consumption were assessed through weekly 7‐day animal‐source food screeners. Grams of intake were assessed through 24‐h recalls conducted at 6-9, 9-12 and 12-15 months of age. Plasma ferritin, soluble transferrin receptor (sTfR) and haemoglobin concentrations were measured at 6-9 and 12-15 months of age. Iron biomarkers were adjusted for inflammation during analysis. At enrolment, each flesh food category was consumed by <5% of children in the past 24 h. Over the next 6 months, small fish, large fish and meat were consumed on 25%, 8% and 6% of days, respectively, with mean usual intakes of <5 g/day. More frequent small fish consumption was associated with lower sTfR (geometric mean ratio [95% CI]: 0.98 mg/L [0.96, 1.00] per 10 percentage point difference) but not ferritin (1.03 µg/L [0.98, 1.07]) or haemoglobin (1.01 g/dL [1.00, 1.01]). Large fish consumption was associated with higher anaemia (prevalence ratio [95% CI]: 1.09 [1.01, 1.19]) and lower iron deficiency (0.96 [0.93, 1.00]) prevalence. Gram intakes of flesh food categories were not associated with any iron or anaemia indicators. Small fish were a primary contributor to flesh food intake in this cohort of Malawian children, although usual portions were small. Fish was associated with modest improvements to iron status, but meat was too infrequent to be associated with anaemia and iron deficiency.